Strategic Planning of Islamic Values-Based Extracurricular Programs for Student Learning Achievement: Perencanaan Strategis Program Ekstrakurikuler Berbasis Nilai-Nilai Islam untuk Prestasi Belajar Siswa - Saragih, Malika Aulia Husnah; Budi, Budi (Halaqa: Islamic Education Journal, 2025)
General Background: Education is central in preparing future generations with competitive competencies. Specific Background: In Islamic institutions, madrasahs play a crucial role in shaping both academic and non-academic excellence, including through extracurricular activities. Knowledge Gap: Prior research has rarely focused on strategic leadership in extracurricular program development, especially in Sumatera Utara’s Islamic schools. Aims: This study aims to explore the strategies implemented by the head of MTs Al-Wasliyah 16 Perbaungan in enhancing student achievement through extracurricular engagement. Results: Through qualitative descriptive methods, results show that structured strategies—vision-based planning, program selection, mentor empowerment, and periodic evaluation—led to an 85% achievement rate, with national-level success in tahfiz and tilawah. Novelty: This is the first study in the region that comprehensively links Islamic leadership principles to extracurricular program outcomes in a madrasah. Implications: The findings offer a strategic model for madrasah leaders to systematically develop student potential beyond the academic curriculum and promote replicable educational leadership practices. Highlights: The madrasa head strategically plans and develops 17 types of extracurricular activities to enhance student performance. Tahfiz Qur’an and Tilawah are the most consistently awarded activities, reaching national-level competitions. Challenges include limited student motivation and inadequate facilities, which are addressed through partnerships and delegation. Keywords: Madrasah Strategy, Student Achievement, Extracurricular Activities, Educational Leadership